Pengaruh Profitabilitas, Transfer Pricing, dan Capital Intensity Terhadap Agresivitas Pajak dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Keysha Anezka Putri; Juita Tanjung (Economic Reviews Journal, 2026)
This study aims to determine the effect of profitability, transfer pricing, and capital intensity on tax aggressiveness moderated by company size in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Using secondary data, the sample technique in this study was selected by purposive sampling method which is included in the non-probability sampling technique with a total of 17 businesses was obtained determined as samples. The analysis method used in this study is panel data regression, with a Random Effect model. By using a tool, namely the Software Eviews 12 program. The results of this study show that profitability variables negatively affect tax aggressiveness. Meanwhile, transfer pricing and capital intensity positively affect tax aggressiveness and company size cannot moderate profitability, transfer pricing, and capital intensity against tax aggressiveness.